The Existence of the Dhikr Tradition Before Migrating In the Perspective of Religious Anthropology - Azis Efendi; Sukron Azhari; Masroer Ch.Jb; Pratiwi Nur; M. Akzomi Zakawali (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The purpose of this research is to look at the dhikr tradition before going away, especially the background of the community always implementing it every year, and to find out the existence of the application of the dhikr tradition before going away by the people of Wakan Village, Jerowaru District, East Lombok Regency, when their children are going to go abroad. This study uses qualitative methods by collecting data through in-depth observation and interviews with parents and young people aged 20-30 years, as well as using previous research that is relevant to this research. The results of the study show that the tradition of dhikr before traveling is a hereditary tradition from the ancestors of the people in Wakan Village. In implementing the tradition of dhikr before going abroad, it becomes a forum for the community to pray for children who go abroad with the aim of a journey to study knowledge that can run smoothly. As well as the impact presented in implementing the dhikr tradition is able to become a social glue for society among other communities, and is able to become the ethos of young people in carrying out their education so that it can be completed quickly. Thus the tradition of dhikr before traveling can become part of religious anthropology, because this tradition is closely related to the religious teachings and culture of the community in Wakan Village, Jerowaru District, East Lombok Regency.